The effects of gonadotropin releasing hormone on reproductive performance of low fertile male rabbits - El Gaafary M.N. (Rabbit production in hot climates, 1994)
Eighteen NZW bucks were used in this experiment. Six of them were fertile and the other twelve bucks were shown to have low libido, bad semen quality and poor fertility records. These twelve bucks were divided randomly into two groups. The bucks in the first group (n
1. International Conference of rabbit production in hot climates, 1994/09/06-08, Cairo (Egypt)